Quran translation: a historical-theological exploration - Boulaouali, Tijani (Penerbit Universiti Kebangsaan Malaysia, 2021)
The traditional prohibition on translating the Quran into other languages is considered to be one of the discussable issues within Islamic theology and jurisprudence. From the eleventh century, when the Islamic state extended politically and geographically, a need arose to understand the Quran, which isthe essence of the Islamic religion. Most non-Arab converts were unable to understand the original Quran text. As a result, they could not understand the true message of their new faith and perform the prescribed worship and practices. This article deals with the topic translating the Quran from a historical and theological point of view. Firstly, some historical factors that lead to the realization of the Quran translation are examined, including the need to understand the Quran both by the new Muslim generations and the People of the Book to defend their own faith against the Islam. Secondly, attention is paid to the theological consensus on prohibiting translation of the Quran into other languages because of its inimitable nature and style. Finally, the problem of the Quran translation is discussed with a focus on the current need for understanding the universal message of the Quran that can only be achieved through translation.